2001
DOI: 10.1080/003655401750174101
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Laboratory Diagnosis of Ulceroglandular Tularemia with Polymerase Chain Reaction

Abstract: Tularemia is a zoonotic disease which, in Scandinavia, is usually acquired through a mosquito bite. As the infecting organism, Francisella tularensis, is highly virulent the culturing of F. tularensis has generally been avoided. PCR offers a safe way to rapidly confirm diagnosis of tularemia. The case of a 9-y-old boy with ulceroglandular tularemia is presented. The diagnosis was made rapidly with DNA amplification from a pus specimen. The efficacy of ciprofloxacin treatment of tularemia in children is also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Although previous studies have demonstrated the utility of PCR assays in analyzing blood samples, swabs from ulcerative lesions, and pus for the presence of FT DNA, 8,10,11,14,[17][18][19][20][21] we describe the first PCR assay designed for use in formalin fixed, routinely processed, archival tissues. Our findings indicate that PCR of processed tissues is a safe, rapid, sensitive, and specific method for the detection of FT in both human and animal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have demonstrated the utility of PCR assays in analyzing blood samples, swabs from ulcerative lesions, and pus for the presence of FT DNA, 8,10,11,14,[17][18][19][20][21] we describe the first PCR assay designed for use in formalin fixed, routinely processed, archival tissues. Our findings indicate that PCR of processed tissues is a safe, rapid, sensitive, and specific method for the detection of FT in both human and animal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…10,14,[17][18][19][20][21] Our goal was to develop a PCR assay that could be used in formalin-fixed, routinely processed tissues, which are (1) safer to handle and (2) allow diagnostic testing even after fixation and processing. We then compared the clinical and pathologic findings with the molecular data.…”
mentioning
confidence: 99%
“…Subsequently, a number of other workers have reported the use of PCR assays for the diagnosis of tularemia (34,93) or for the analysis of environmental samples (16). These PCR-based tests might also be safer than tests which involve the culture of bacteria (162).…”
Section: Detection and Diagnosismentioning
confidence: 99%
“…Detection of F. tularensis in clinical specimens may also be achieved by using fluorescencelabeled antibodies. PCR-based methods have been proposed for use in the detection of F. tularensis DNA in human skin lesions or in the blood of experimentally infected mice (18,21). These procedures permit a more rapid diagnosis but are usually performed in reference laboratories.…”
mentioning
confidence: 99%